1993
DOI: 10.1161/01.cir.88.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Platelet cyclic GMP. A potentially useful indicator to evaluate the effects of nitroglycerin and nitrate tolerance.

Abstract: These results indicate that platelet cGMP can be used as an indicator for in situ evaluation of nitroglycerin effects and that patients who have received nitrates develop nitrate tolerance, which affects intracellular production of cGMP and vasodilation in the response to nitroglycerin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
1

Year Published

1994
1994
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 43 publications
2
21
1
Order By: Relevance
“…Kukovetz & Holzmann (1986) showed that the in vitro exposure of vascular tissue to NTG caused a dose-related increase in intracellular cyclic GMP which correlated with the simultaneous relaxation of the preparation, with both effects being impaired after prolonged incubation with NTG. Similar findings were reported in vivo (Watanabe et al, 1993) where the increase in platelet cyclic GMP correlated with epicardial coronary artery diameter. Both platelet cyclic GMP and the coronary artery changes were less pronounced in those patients receiving nitrate therapy.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Kukovetz & Holzmann (1986) showed that the in vitro exposure of vascular tissue to NTG caused a dose-related increase in intracellular cyclic GMP which correlated with the simultaneous relaxation of the preparation, with both effects being impaired after prolonged incubation with NTG. Similar findings were reported in vivo (Watanabe et al, 1993) where the increase in platelet cyclic GMP correlated with epicardial coronary artery diameter. Both platelet cyclic GMP and the coronary artery changes were less pronounced in those patients receiving nitrate therapy.…”
supporting
confidence: 88%
“…and although they do not appear to possess the enzyme required for the direct conversion of NTG, it is believed that sufficient NO can be released from NTG by the vascular tissue enzyme to enable activation of the platelet guanylate cyclase (Gerzer et al, 1989). Thus platelet cyclic GMP might be an index of the tone, or state of relaxation of the vessels (Watanabe et al, 1993;Fung et al, 1993) following intravenous NTG.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that there was a good correlation between the percent increase in platelet cGMP level and the percent dilatation of coronary arteries, and that the intracellular production of platelet cGMP level was decreased during continuous nitrate therapy. 8 These observations suggest that nitrate tolerance is related to blunted vasodilation due to the attenuation of intracellular production of cGMP in response to NTG. Parker et al suggested that nitrate therapy is associated with both neurohormonal activation and plasma volume expansion and that these responses may play a role in the loss of nitrate efficacy.…”
Section: Nitrate Tolerancementioning
confidence: 95%
“…The pellet was suspended in modified Tyrode's solution (containing 0.35% bovine serum albumin and 5 mmol/L HEPES, pH 7.35) to obtain a final platelet count of 2-3×10 6 platelets/ l. Samples were stored frozen at -70°C until analysis. 8 …”
Section: Preparation Of Platelet Cgmpmentioning
confidence: 99%